![](/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
x2 + 4x -y2 = 1
=> x2 + 4x - y2 + 4 = 1 + 4 = 5
=> (x2 + 4x + 4) - y2 = 5
=> (x+2)2 - y2 = 5
=> (x+2-y)(x+2+y) = 5
Ta có:
1.5=5
mà x+2-y < x+2+y
=> \(\hept{\begin{cases}\text{x+2-y=1}\\\text{x+2+y}=5\end{cases}}\)=> \(\hept{\begin{cases}x-y=-1\\x+y=3\end{cases}}\)
Từ x-y = -1 => x = y - 1
Thay x = y - 1 vào x + y, ta có:
x + y = y - 1 + y = 3
=> 2y - 1 = 3
=> 2y = 4 => y=2
=> x = 2 - 1 = 2
Vậy x=2; y = 1 thì x2 + 4x -y2 = 1
![](/images/avt/0.png?1311)
chó nguchó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
chó ngu
![](/images/avt/0.png?1311)